THE ROLE OF MODERN TECHNOLOGIES AND THE INTERNET IN THE ENGLISH LANGUAGE FOR PRESCHOOL CHILDREN - Badriyeva Sevinch Asqariddinova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstrack: As you read this article, you will be able to learn about modern technologies and the role of internships in teaching English to preschoolers.